Deixe-me ser eu mesma: uma análise sobre o papel social das mulheres na Shoah em O diário de Anne Frank - Menezes, Jackyelle Firmino (2023)
The Shoah was engineered, systematized and perpetrated by the Nazis with the aim of systemic persecution, socioeconomic exclusion, expropriation, forced labor and extermination of Jews, Gypsies, people with disabilities, black individualw, Poles, Russians, Communists, Socialists, Jehovah’s Witnesses and men gays. It was a period marked by diverse changes and writing was a conductor of hope, support and survival. The act of witnessing, through writing, experiences as victims in spaces such as hideouts, ghettos, concentration camps was a way of confronting and resisting the Nazi system. Anne Frank, a Jew girl who was a victim of Nazi inhumanity, wrote The Diary of Anne Frank over a two-year period while she and her family resided in a hideout called the Annex in Amsterdam, Holland. In the work The diary of Anne Frank, Anne narrates and witnesses the events of her own life in which she emphasizes her Jewish condition and female condition. With that, we have a testimony of a young Jewish woman who faced attempts at silencing, erasing and extermination. From this, this research aims to analyze the female role of women to the Shoah from the perspective of Anne Frank. Therefore, the theoretical contribution of this research focuses on author-witnesses such as Primo Levi, Charlotte Delbo, Olga Lengyel, Miep Gies, Nanette Konig, Willy Lindwer and Eva Schloss, and on theorists Saul Friedlander, Márcio Seligmann-Silva, Pierre Vidal -Naquet and Georges Didi-Huberman. The research also dialogues with the critical fortune of The Diary of Anne Frank. In the proposed analysis, we reflect on the perception Anne Frank developed regarding the social role of women during the Shoah. Through her writings, Anne addresses the condition faced by women of that time, subjected to prevailing patriarchal structures. Furthermore, she fosters the discussion about a new social role for women, presenting a perspective directed toward these transformations, aiming to achieve independence, recognition, and valorization of women.